PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP PENGUNGKAPAN INTELLECTUAL CAPITAL PADA PERUSAHAAN IC INTENSIVE YANG TERDAFTAR DI BEI - Dista Amalia Arifah (Universitas Muhammadiyah Semarang, 2011)
This study aims to analyze the influence of audit committee characteristics, which is consists of : audit committee membership, audit committee independence, independent commissioner proportion, audit committee chief and audit committee competence on the intellectual capital disclosure, companies used in the category of intensive ICs at BEI in 2009, also considering the control variables. The population included in the category of IC intensive companies amounted to 176. Sampling using a purposive sampling method and obtained 73 samples that meet the criteria.The data used in this study is secondary data, the annual report of the company in 2009 and processed by multiple regression. ICs disclosure acquisition data using content analysis techniques to the analysis unit that has been determined, the IC disclosure have been acquired in quantity and quality terms.The results showed that among audit committee characteristicsthat are used only audit committee membershipand audit committee chief which affects the IC disclosure in quantity terms. While two other control variables which are size and profitability, showed different results. Only size was affected significantly in quality IC disclosure terms.